Application of 16 bit image lossy compression based on the JPEG standard - Nini XU; Chenguang LI (Dianxin kexue)
The principle and detailed process of 16 bit image lossy compression were given. The data of 16 bit image is large and JPEG does not support the 16 bit image compression，which makes it inconvenience in 16 bit image’s storage and transmission. Based on the scheme of JPEG compression，the statistical model was expended （improving the tables of statistical model for DC coefficient coding and statistical model for AC coefficient coding respectively）. This made it can deal with the data of 16 bit and realized the ideal of the compression of 16 bit static images. The quantization table used was generated based on the Luminance quantization table in JPEG. The encoder adopted was QM arithmetic encoder. An objective evaluation standard PSNR was chosen to evaluate the quality of the decompressed images.